Electromagnetic Compatibility in Railways Analysis and Management - Ogunsola, Ade.; Mariscotti, Andrea; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
A railway is a complex distributed engineering system: the construction of a new railway or the modernisation of a existing one requires a deep understanding of the constitutive components and their interaction, inside the system itself and towards the outside world. The former covers the various subsystems (featuring a complex mix of high power sources, sensitive safety critical systems, intentional transmitters, etc.) and their interaction, including the specific functions and their relevance to safety. The latter represents all the additional possible external victims and sources of electromagnetic interaction. EMC thus starts from a comprehension of the emissions and immunity characteristics and the interactions between sources and victims, with a strong relationship to electromagnetics and to system modeling. On the other hand, the said functions are achieved and preserved and their relevance for safety is adequately handled, if the related requirements are well posed and managed throughout the process from the beginning. The link is represented by standards and their correct application, as a support to analysis, testing and demonstration.
Railway traction systems -- Signalling and Communication systems 108 -- EMC Management 191 -- EMC Assurance -- Standards and standardization -- Applied Electromagnetic Theory -- Earthing, bonding and cable layout.
Keywords: Engineering; Computer engineering; Electronics; Production of electric energy or power; Engineering; Electrical Engineering; Electronics and Microelectronics, Instrumentation; Power Electronics, Electrical Machines and Networks